192k views
1 vote
Solve for b. -11b+7 = 40−11b+7=40

User Whozumommy
by
4.9k points

2 Answers

5 votes

Answer:

b= -3

Explanation:

So uh it was not -11b+7 = 40−11b+7=40

it was -11b+7 = 40 the equasion was probably just copy pasted twice.

Sorry im late i just got this question on khan acadamey

hope this helps

User Alex Willrock
by
5.5k points
5 votes

Answer:

This equation is false

Explanation:

Well,

-11b + 7 = 4 - 11b + 7 = 40

combine like terms

-11b + 7 = -11b + 3 = 40

Communicative property

-3 to both sides

-11b + 4 = -11b = 40

-4 to both sides

-11b = -11b = 36

+11b to both sides

0 = 36

0 is not equal to 36 meaning that this equation is false.

Thus,

the equation given is false.

Hope this helps :)

User Suliman Farzat
by
5.5k points